Composição florística de angiospermas no carste do Alto São Francisco, Minas Gerais, Brasil - De Melo, Pablo Hendrigo Alves; Lombardi, Julio Antonio [UNESP]; Salino, Alexandre; De Carvalho, Douglas Antônio (My University, 2013)
The occurence of carbonatic rocks defines a typical type of relief, called karst, that, by its geomorphology and hydrology, usually differs from the surrounding landscape. In the upper São Francisco river basin, some striking remnants of vegetation associated to karst can be found, which are locally knwon as Mata de Pains. In this region, a mosaic of different physiognomies, including forests and open areas, which present noteworthy plant diversity, composes the vegetation. The aim of this study is to provide an inventory of angiosperm species in areas of carbonatic rocks outcrops in the upper São Francisco river basin karst region, as well as analyze the floristic relationship of the study area with different Brazilian phytogeographic domains. Fieldwork was performed during the period of 2002 a 2006, when collections of fertile speciemns were done in areas associated to carbonatic rock outcrops. During the study, 1512 exsicates were incorporated to BHCB herbarium collection. A total of 456 angiosperm species were inventoried, distributed in 299 genera and 77 families. Herbaceous habit was better represented, with 161 species, followed by shrubs and trees (111 species each) and lianas (73 species). The flora of the study area presents more influence of the Mata Atlântica domain (Atlantic Rain Forest), followed by, in order of importance, Cerrado, Amazonia, Caatinga, Pantanal and Pampa. Floristic surveys in different karst regions inserted in different phytogeographic domains may, together, provide useful information in understanding the phytogeografic history of Neotropical vegetation.
Floristic composition
Keywords: Dolomite; Flora; Limestone outcrops; Mata de Pains; Phytogeographic domains